1996
DOI: 10.1109/2945.537309
|View full text |Cite
|
Sign up to set email alerts
|

Glyphs for visualizing uncertainty in vector fields

Abstract: Environmental data have inherent uncertainty which is often ignored in visualization. Meteorological stations and doppler radars, including their time series averages, have a w ealth of uncertainty information that traditional vector visualization methods such as meteorological wind barbs and arrow glyphs simply ignore. We h a ve d e v eloped a new vector glyph to visualize uncertainty in winds and ocean currents. Our approach is to include uncertainty in direction and magnitude, as well as the mean direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
135
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(135 citation statements)
references
References 16 publications
0
135
0
Order By: Relevance
“…Studies that do not appear in our list include, e.g. conceptual evaluations that use heuristics derived from general guidelines and rules for data visualisation coined by Bertin, Tufte, Ware and Chambers (Riveiro, 2007a;Riveiro, 2007b;Wittenbrink et al, 1996;Zuk and Carpendale, 2006). Such studies, while not our focus here, do provide basic statements on the usability of different methods and therefore can help to choose suitable visualisation techniques.…”
Section: N Coincident/adjacentmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies that do not appear in our list include, e.g. conceptual evaluations that use heuristics derived from general guidelines and rules for data visualisation coined by Bertin, Tufte, Ware and Chambers (Riveiro, 2007a;Riveiro, 2007b;Wittenbrink et al, 1996;Zuk and Carpendale, 2006). Such studies, while not our focus here, do provide basic statements on the usability of different methods and therefore can help to choose suitable visualisation techniques.…”
Section: N Coincident/adjacentmentioning
confidence: 99%
“…Pang and colleagues designed glyphs to represent data and uncertainty in combination. In an early study by Wittenbrink et al (1996), the authors compared arrow glyphs including uncertainty information ('verity visualisation') to common arrow glyphs without uncertainty and found that they encoded bearing, magnitude, and uncertainty with almost the same effectiveness as with the simple arrow glyphs. In the study by Newman and Lee (2004) already mentioned above, three extrinsic techniques received the highest ratings regarding effectiveness: multi-point, ball and arrow glyphs.…”
Section: Intrinsic/extrinsicmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Cedilnik and Rheingans [1] looked at different ways of imparting uncertainty over 2D fields using procedural methods to distort overlaid grid lines, Interrante [3] discussed how one might use natural textures over a map to show uncertainty, Djurcilov and Pang [2] looked at different ways of incorporating uncertainty information in contour lines and isosurfaces of sparse data sets, Wittenbrink et al [11] included uncertainty in direction and uncertainty in magnitude into glyph designs, and Pang et al [7] described some general methods for incorporating uncertainty into visual displays.…”
Section: Introductionmentioning
confidence: 99%